CONCEPTUAL NOTES REGARDING THE SPORTS IN NATURE (Fiep Bulletin - online, 2015)
The increase in the number of possibilities of body practices generates new problems for the sport theories. Among them we detach the conceptual problems arising from the present expansion of activities made in the middle of nature. The contemporarily of these practices is claiming for  more attention and careful exam from the human sciences. However, the study developments on this area always face a certain conceptual confusion generated in its inside. The lack of consensus and of the terminology precision generates some additional difficulties for the investigations. Our objective in this work is to point out some theoretical and conceptual dilemmas placed by the  process of using the open nature for the sports practices.
Keywords: leisure; sports in open nature; concept.